PEMBERDAYAAN REMAJA PEREMPUAN MELALUI PEMANFAATAN UBI JALAR SEBAGAI MASKER WAJAH ALAMI BERBASIS POTENSI LOKAL DI DESA KAMPUNG SAWAH, KECAMATAN BESITANG, KABUPATEN LANGKAT - Fauzi Kurniawan; Tegar Anggi Handika; Angel Sagala; Anisa Azmi; Cindy Nadya; Mariana Sinaga; Marisa Nabila; Oriza Salsabila; Rista Triwani; Sondang Dioranta (STKIP Subang, 2026)
This study aims to describe efforts to empower adolescent girls through the utilization of sweet potatoes (Ipomoea batatas L.) as natural facial masks based on local potential in Kampung Sawah Village, Besitang District, Langkat Regency. This study employed a descriptive qualitative approach with data collection techniques comprising participatory observation, in-depth interviews, and documentation. The research subjects were adolescent girls aged 15–22 years residing in Kampung Sawah Village who actively participated in the training activities for making facial masks from sweet potatoes. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña (2014), encompassing data condensation, data display, and conclusion drawing. The results indicate that: (1) the training activities successfully enhanced participants’ knowledge and skills in processing sweet potatoes into value-added products; (2) participants demonstrated high enthusiasm and active participation throughout the training process; (3) the facial mask products yielded good quality in terms of texture, ease of application, and natural ingredient content; and (4) the activity opened opportunities for the development of home-scale businesses based on local raw materials. Thus, empowerment based on local potential through skills training proved effective in improving the creativity, independence, and productivity of adolescent girls. The findings of this study are expected to serve as a reference for the development of sustainable community empowerment programs.